Inter-relações entre nematoides, fungo e a cultura da seringueira - Takahashi, Vanessa dos Santos Paes [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The heveiculture plays an important hole in São Paulo State, which produces more than 50% of the total Brazilian natural rubber production. The nematodes are important pathogens that have been causing significant losses to the crops. In the literature there is not many papers related to nematodes in rubber trees, especially about Pratylenchus brachyurus, the nematode most important to Brazil nowadays. In this sense the objectives of this work were: a) to do a survey of the nematodes occurrence in rubber trees nurseries in São Paulo State, b) study the resistance and tolerance of rubber trees used as rootstock to Pratylenchus brachyurus and Meloidogyne exigua, c) study the interactions between M. exigua or P. brachyurus, and Lasiodiplodia theobromae in rubber trees seedlings in two moisture conditions. As the results of the survey it was found that Meloidogyne and Pratylenchus were the most frequent and in high densities at the samples. The species identified were M. incognita, M. exigua, P. brachyurus e R. reniformis. Among them, P. brachyurus was the most frequent specie found at rubber trees roots and must be consider as a key nematode to the crop. This work was also the first report of M. exigua causing damage to the rubber trees seedlings in São Paulo State. The second experiment carried out at green house conditions, have demonstrate that M. exigua caused more pronounced damage to the rubber tree rootstocks 'GT 1', 'PB 235', 'PB 217', 'RRIM 501', 'PR 255', 'IAN 873', 'RRIM 600' e 'TJ 1', and all of them were intolerant and susceptible to M. exigua e P. brachyurus. Finally, at the third experiment also carried out in green house conditions, was observed that the biometrics characteristics and the nematodes were affected by the reduction in 50% (CC) of pot capacity. There was an interaction between L. theobromae and P. brachyurus in the increase of plant diameter. There was not an interaction among ...

A heveicultura assume papel de destaque no estado de São Paulo, que responde por mais da metade da produção Brasileira de borracha natural. Os nematoides são importantes patógenos que vêm causando perdas significativas à produção de diversas plantas cultivadas. Na literatura, encontram-se poucos trabalhos acerca dos nematoides na cultura da seringueira, principalmente quando se trata de Pratylenchus brachyurus, um nematoide de grande importância atual no Brasil. Neste sentido os objetivos deste trabalho foram: a) realizar um levantamento dos nematoides em viveiros de produção de mudas de seringueira do estado de São Paulo, b) avaliar a resistência e tolerância de plantas de seringueira utilizadas como porta enxertos à Pratylenchus brachyurus e Meloidogyne exigua, c) estudar a interação entre M. exigua ou P. brachyurus, e Lasiodiplodia theobromae em mudas de seringueira em duas condições hídricas. Os resultados do levantamento demonstram que os nematoides de maior frequência e densidade foram Meloidogyne e Pratylenchus. As principais espécies identificadas foram M. incognita, M. exigua, P. brachyurus e Rotylenchulus reniformis. Destes, P. brachyrus foi a espécie mais frequente nas amostras das raízes das mudas de seringueira e deve ser considerado praga chave da cultura. Este trabalho também foi primeiro relato de M. exigua no Estado de São Paulo causando danos em mudas de seringueira. O segundo experimento realizado em casa de vegetação, demonstrou que M. exigua causou reduções mais pronunciadas na altura e no diâmetro de caule dos porta-enxertos de seringueira 'GT 1', 'PB 235', 'PB 217', 'RRIM 501', 'PR 255', 'IAN 873', 'RRIM 600' e 'TJ 1', sendo todos considerados intolerantes e suscetíveis a M. exigua e P. brachyurus. E por fim, no terceiro experimento, realizado em casa de vegetação, observou-se que tanto as características biométricas, quanto os nematoides foram afetados...
Keywords: Seringueira; Seringueira - Mudas; Nematoda em plantas; Fungos; Meloidogyne exigua; Rubber plants